Conduct post-accident injuries: perception and knowledge of primary care nurses in Fortaleza - Feijão, Alexandra Rodrigues (2011)
The aim of this work is to investigate nurses’ knowledge about the measures to be taken before an accident with sharp and cutting objects. It is a descriptive exploratory study carried out with 36 nurses working in primary healthcare units in the city of Fortaleza, Ceara, Brazil. It was found out that: eight out of the 14 injured people reported to have followed some post-accident behavior with sharp and cutting objects: they actually washed the area immediately and conducted serological tests; looked for a hospital which is specialized in infectious diseases; some serological tests were performed in the professional as well as in the source patient or simply followed the own procedures of the institutions they work for. Regarding the perception of nurses as to conduct post-accident with sharp and cutting objects, it was found out that 32 nurses were considered experts on the procedures and 30 of them felt to be ready to act before an accident at work. Knowledge of conduct recommended by the Ministry of Health is required for professionals in primary care in particular the nurse since he/she is often exposed to risks at work.